1996
DOI: 10.1002/ardp.19963291105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Activity of the Glutathione Analogue γ‐(L‐γ‐Oxaglutamyl)‐L‐cysteinyl‐glycine

Abstract: An efficient synthesis of the backbone modified glutathione analogue gamma-(L-gamma-oxaglutamyl)-L-cysteinyl-glycine (7), characterized by the presence of an urethane O-CO-NH linkage replacing the gamma-glutamylic CH2CO-NH fragment is described. The new analogue has been fully characterized by 1H- and 13C-NMR, and FAB-MS. Compound 7 was tested for inhibition of gamma-glutamyl-transferase activity and was found to be a non-competitive inhibitor of hog kidney gamma-glutamyltransferase (EC 2.3.2.2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…4.4ppm) (Lift et al, 1996). A characteristic feature (Theriault et al, 1984;Calcagni et al, 1996) of the 13C-NMR spectrum of 6 is represented by the resonances of the two Cys fl-carbon atoms (28.15 and 28.80 vppm) which are shifted at higher field as compared with the corresponding atoms in the disulfde precursor 5 (49.92 and 45.77 6 ppm). The electrospray mass spectrum (ES-MS) of 5 shows the formation of both M + H + and 2M + H + species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4.4ppm) (Lift et al, 1996). A characteristic feature (Theriault et al, 1984;Calcagni et al, 1996) of the 13C-NMR spectrum of 6 is represented by the resonances of the two Cys fl-carbon atoms (28.15 and 28.80 vppm) which are shifted at higher field as compared with the corresponding atoms in the disulfde precursor 5 (49.92 and 45.77 6 ppm). The electrospray mass spectrum (ES-MS) of 5 shows the formation of both M + H + and 2M + H + species.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of our studies on the synthesis of glutathione (GSH) analogues (Luisi et al, 1993;Calcagni et al, 1995;Calcagni et al, 1996) we are investigating structures containing cyclic frameworks centered at the Cterminal moiety. Although a number of chemical modifications have been performed on this molecule (Chen et al, 1986;Douglas, 1989;Xie et al, 1991;Embrey et al, 1994;GrOger et al, 1996), literature examination revealed that no data are available on GSH analogues containing a Cys residue replacing the C-terminal Gly and giving rise to a -Cys-Cys sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The pseudopeptide was prepared essentially after our reported protocol, with the urethanic junction made up by convenient functionalization of a protected serine residue (Scheme 2) 29 . By following the aforementioned conditions for heteroaryl substitution, the S-conjugate was collected in only moderate yields, together with significative amounts of nonreacted starting thiol.…”
Section: Methodsmentioning
confidence: 99%
“…Over the years we designed a variety of GSH mimics and derivatives characterized by amino acid substitution and/or bioisosteric replacements of the g-glutamyl linkage, addressed to enhance both metabolic resistance and affinity to GST binding sites, through the attribution of specific chemical and conformational properties to the modified GSH backbone [27][28][29][30][31][32][33][34] . Among these, the g-oxa-glutamyl (Glo) analog of GSH, H-Glo[Cys-Gly-OH]-OH, deserves particular attention for more than one reason: (1) as expected, the replacement of the scissile g-glutamyl-cysteinyl peptide bond with the OCONH unit assures resistance to g-GTmediated hydrolysis 29,35 ; (2) the substitution does not sensibly alter the physico-chemical properties of the tripeptide; (3) groups crucial for binding to the G-site resemble those of the natural ligand, with the H-bond donor/acceptor potential of the GSH backbone fairly maintained and (4) more importantly, S-conjugates of this urethane mimic of glutathione have been shown to inhibit MRP1 36 . Thus we report here a straight preparation of the glutathione conjugate H-Glu[Cys(NBD)-Gly-OH]-OH (GS-NBD, 1) and the synthesis of its new analog H-Glo[Cys(NBD)-Gly-OH]-OH or (OCONH) GS-NBD (5), to be comparatively evaluated as inhibitors of human GSTP1-1 and M2-2.…”
Section: Introductionmentioning
confidence: 99%
“…In the cited field, a new group of glutathione analogues were reported containing urea [14] or urethane [15] groups replacing the native γ -glutamyl isopeptide bond, which is the cleavage site of γglutamyl transpeptidase (γ -GT) [16][17][18][19][20] as well as a structural determinant in GSH recognition and binding to biomacromolecules [21,22]. Both these amide bond surrogates present stability towards enzymatic hydrolysis and maintain a planar structure at the key site; therefore, the sp 3 aminomethylene CH 2 NH group was of interest to mimic the tetrahedral intermediate of γ -Glu-Cys peptide bond hydrolysis [23].…”
Section: Introductionmentioning
confidence: 99%